Implementasi Pengolahan Sampah Dengan Metode Komposting Dan Ecobrick Di Pondok Pesantren Nidhomuddin - Anwar, Hasrul; Ulya, M. Ridho; Sari, Devi Kurnia; Djanna, Miftahul; Mayasari, Rizka; Utari, Ririn; Putra, Ramadani Diana; Sugiarto, Bagas Gangsar (Pakis Journal Institute, 2024)
The waste problem is one of the main challenges faced by Indonesian society, including at the Nidhomuddin Islamic Boarding School, Negara Ratu Village, Natar, South Lampung. Waste management in this area still needs to be optimized. To overcome this, this activity aims to provide education to students regarding the processing and use of organic and inorganic waste. The methods applied in this activity include composting for organic waste and making ecobricks for plastic waste. The training took place on 14–19 September 2023 and was attended by 40 students. The results of the training show the high enthusiasm of the participants, which is expected to encourage increased awareness and participation of students in independent waste management.